Analisis Tingkat Motivasi Aktivitas Fisik Siswa di Masa Pandemi Covid-19 Bandung - Alhadi, Dzaki; Syafriani, Rini (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2023)
Sports motivation for post -pandemic students influences this post -pandemic sports activity. This study aims to describe the comparison of the sports motivation of students after Pandemi Covid-19 in Bandung. The research method used is a quantitative descriptive method. The population in this study were high school students and students in Bandung. The sample in this study was students and students who were active in post -Pandemic schools in Bandung. In returning the sample, researchers used purposive sampling. This study uses questionnaire and survey instruments. Data analysis uses the Statistics Test of Smirnov Colmogrov for testing data normality and Independent T Test tests to find out the difference in motivation between sex during exercise after Pandemic Covid-19 in the city of Bandung. Based on the data statistical test data, it is known that the sig (2-tailed) value is 0.001> 0.05, it can be concluded that with the significant difference between the sport motivation of male and female students who have motivation when exercising. Because of this significant difference, it can be seen that the motivation of male and female students affects during sports activities.